Parental Stress Scale: Adaptation on the Russian-Speaking Sample of Schoolchildren’s Mothers - Bochaver, A.A.; Akhmedjanova, D.R.; Bayramyan, R.M.; Polivanova, K.N. (Socialʹnaâ Psihologiâ i Obŝestvo, 2024)
Objective. Adaptation of the Parental Stress Scale by J. Berry and V. Jones on a sample of mothers of Russian schoolchildren - first and fourth grade students of elementary schools in Nizhny Novgorod and the Nizhny Novgorod region. Background. Modern parenting research highlights the complex nature of parenting experiences, the diversity of parental practices, the changes associated with the child's upbringing and the dynamics of the family system, and the combination of both positive and negative emotions in parenting. However, there is a noticeable shortage of tools in the Russian-language literature to measure both parental satisfaction and parental stress. Study design. The study was conducted using an online survey within the "Longitudinal study of factors of school failure", implemented in Nizhny Novgorod and the Nizhny Novgorod region. Participants. The study included a sample of 900 mothers of fourth grade and 1120 mothers of the first grade school students. Measurements. Exploratory and confirmatory factor analysis and McDonald's Omega coefficients were used for psychometric data analysis. The PERMA Profiler questionnaire and correlation analysis were used to assess validity based on convergent and discriminant evidence. The data was analyzed in the Jamovi 2022 and R programs. Results. Factor analyses of the internal structure suggest two factors, including 8 items each. The subscales "Parental stress" and "Parental satisfaction" demonstrate a high level of internal consistency. The assessment of validity based on the convergent and discriminant evidence confirms the reliability and validity of the instrument. Conclusions. The scale demonstrates good psychometric properties and can be used for parenting research, as well as in applied projects to improve parental competence and emotional support for parents. Цель. Адаптация методики Шкала родительского стресса (Parental Stress Scale) Дж. Берри и У. Джонса на выборке матерей российских школьников - учащихся первых и четвертых классов общеобразовательных школ Нижнего Новгорода и Нижегородской области. Контекст и актуальность. Современные исследования родительства подчеркивают комплексный характер переживаний родителей в ходе воспитания детей, разнообразие родительских практик, изменения, сопряженные с взрослением ребенка и динамикой семейной системы, и сочетание как позитивных, так и негативных эмоций в опыте родительства. Однако на текущий момент в русскоязычной литературе ощущается заметный дефицит инструментов, позволяющих измерять как степень удовлетворенности собой как родителем, так и уровень родительского стресса. Дизайн исследования. Исследование проводилось с помощью онлайн-опроса в рамках лонгитюдного исследования факторов школьной неуспешности, реализуемого в Нижнем Новгороде и Нижегородской области. Участники. Исследование включало 900 матерей учащихся четвертых классов, а также 1120 матерей первоклассников. Методы (инструменты). Для психометрического анализа данных были использованы эксплораторный и конфирматорный факторный анализ, коэффициент омега Макдональда. Для оценки конвергентных и дискриминантных связей использовался опросник благополучия «PERMA Profiler» и корреляционный анализ. Данные обрабатывались в программах Jamovi 2022 и R. Результаты. Факторный анализ структуры опросника показывает два фактора, к каждому из которых относятся 8 пунктов. Субшкалы «Родительский стресс» и «Родительская удовлетворенность» демонстрируют хороший уровень внутренней согласованности. Оценка валидности на основе конвергентных и дискриминантных связей подтверждает надежность и валидность инструмента. Основные выводы. Шкала демонстрирует хорошие психометрические показатели и может использоваться для исследований родительства, а также в прикладных проектах по повышению родительской компетентности и эмоциональной поддержке родителей.